426 Economics of replacing N fertilization with legumes in bermudagrass pastures for growing beef steers in the Southeastern USA. (7th December 2018) - Beck, P; Weiss, C; Hubbell, D; Hess, T; Kegley, E; Jennings, J; Gadberry, S
Abstract: In order to determine the economics of replacement of N fertilization with legumes in bermudagrass pastures for growing steers, alfalfa (ALF, cv Rebel, 28 kg/ha) or clovers (CLVR, 2.2 kg/ha white clover; cv. Regal Graze, Cal/West Seeds and 8.8 kg/ha red clover, cv. Morningstar, Cal/West) were overseeded into bermudagrass for grazing by growing calves. Alternatively, bermudagrass monocultures were fertilized with 0, 56, or 112 kg/ha of N each year. Steer body weight gain/ha were 265, 357, 410, 570, 560 kg/ha for 0N, 56N, 112N, ALF, and CLVR, respectively. Alfalfa seeding cost $302/ha in yr 1, CLVR seeding cost $106/ha in yr 1 and 3. Costs of pasture and livestock management were $378, $482, $570, $504, and $449/ha for 0N, 56N, 112N, ALF, and CLVR, respectively. Annual net returns were $136, $212, and $224 for 0N, 56N, and 112N, respectively. For ALF, net return was $323/ha in yr 1 and $849/ha thereafter. Net returns for CLVR were $531/ha for yr 1 and 3 and $637/ha for yr 2 and 4. The Risk Solver Platform Excel plugin (Frontline Solvers, Incline Village, NV) was used to model the net returns of grazing systems and define the most profitable system for the 4-yr persistence horizon of the ALF system for a 40-ha farm. The solution indicated that the most profitable production system would be overseeding the entire 40-ha operation with CLVR resulting in net return of $94, 600 over 4-yr. Net return would be decreased to $89, 620 if 24-ha were planted to ALF and 16-ha planted to CLVR, and net returns would be reduced to $36, 400 with the 112 kg N/ha application rate. This model indicates that clovers are an economically viable alternative to N fertilization in the Southeastern US.